Decades of cough: delayed recognition of atypical cystic fibrosis in an adult patient. Issue 6 (June 2020) - Chandel, Abhimanyu; Pak, Kevin; Dooley, Sean; Salazar, Krystle
We present a case of a 30-year-old male diagnosed with atypical cystic fibrosis. This report demonstrates the heterogeneity of the presentation of this common genetic disease.